Pendeteksian Fraud pada Laporan Keuangan melalui Narsisme, Politisi CEO dan Kepemilikan Manajerial - Pamungkas Faizal Randi; Sekar Akrom Faradiza (Department of Accounting-Faculty of Economic and Business (FEB), 2022)
Many researches on fraudulent financial reporting have been carried out. It started with the fraud triangle theory which developed into a fraud diamond and is now known as the fraud pentagon. One of the factors in the fraud pentagon is arrogance. Arrogance is a trait arrogant in someone who believes that company rules or company controls do not apply to him. This study aims to examine the arrogance factor as measured by three variables, namely narcissism, CEO politicians and managerial ownership. The sample used in this study is a manufacturing company that listed on the IDX using 2018-2019 data. Data were analyzed using multiple linear regression. The results of this study indicate that arrogance as measured by narcissism has a positive effect on fraudulent financial reporting. The results of this research imply that users of financial statements should be more careful when financial statement present a lot number of CEO pictures because they have a greater possibility of fraud.